The SAGE Handbook of Outdoor Play and Learning - Waller, Tim; Arlemalm-Hagser, Eva; Sandseter, Ellen Beate Hansen; Lekies, Kristi; Wyver, Shirley; Lee-Hammond, Libby (SAGE Reference, 2017)
There has been a growing academic interest in the role of outdoor spaces for play in a child's development. The SAGE Handbook of Outdoor Play and Learning represents a coordinated and comprehensive volume of international research on this subject edited by members of the well-established European Early Childhood Education Research Association Outdoor Play and Learning SIG (OPAL). Chapters written by authors from Europe, North and South America, Australasia, and Asia Pacific countries are organised into six sections: Theoretical Frameworks and Conceptual Approaches for Understanding Outdoor Play & Learning, Critical Reflections on Policy and Regulation in Outdoor Play & Learning, Children's Engagement with Nature, Sustainability and Children's Geographies, Diverse Contexts and Inclusion in Children's Outdoor Play Environments, Methodologies for Researching Outdoor Play and Learning, Links Between Research and Practice.